A qualitative exploration of the work of embodiment in adolescent girls with obesity. Issue 5 (5th July 2016) - Liné, C.; Moro, M. R.; Lefèvre, H.; Thievenaz, J.; Lachal, J.
Summary: Social representations generally associate obesity, especially in adolescent girls, with sedentariness, lack of self‐control and laziness. These girls thus have substantial problems of self‐esteem. Dietary, lifestyle and behavioural approaches alone cannot address this issue, for they do not apprehend all of the complexity of obesity. This qualitative study is based on a dual observation: that the work performed by adolescents is unrecognized and that the body is not considered as a subject of analysis. It raises the question of the corporality of these teens through an original perspective: that of the perspective of their organization of actions on, to and by the body, in specific situations. The objective is to have access to the corporal experience of young girls with obesity, so that we can understand and support them better. The data come from semi‐directive interviews with 10 adolescent girls with obesity. The content was analysed in terms of concepts of professional didactics (a branch of educational psychology) and enaction. Five situations were identified from these interviews: the first, shopping with friends, concerns actions by the subjects towards their bodies; the other four are enacted actions: conduct towards a normal‐weight person, conduct in public transportation, performing physical activity, and eating. The results show the work of these young women with obesity, the means they mobilize to live in their bodies and their considerable efforts of embodiment. Recognition of this work should help to enhance their self‐esteem. Treatment and support may take this dimension of work into account and help them to become aware of the efforts they make every day.